Advantages of using interactive board at the classes of Higher Mathematics in technical university - Irina N. Pavlova; Michail A. Yevdokimov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Today the discrepancy between the amount of knowledge that a learner should get according to the program and the time available for this encourages professors to look for productive ways of educational process organization that would help to avoid a decline in the quality of teaching as a whole and increase the degree of information perception in particular as well as contribute to students’ cognitive and creative activity development. Taking into account the global informatization of modern society, especially the fact that usage of information and computer technologies for modern people is not only a part of their everyday life but it also captures many spheres of life of the whole society including the sphere of education, it makes impossible imagining of effective academic activity methods without information technologies active introduction. In conditions of ubiquitous informatization of education the use of modern information technologies in the training process including the use of such a modern computer platform as an interactive board helps to achieve these goals. Application of this innovation device during higher mathematics lessons gives opportunity to improve the process of the subject studying, makes it more intensive, dynamic, informational and graphical and as a result it makes the lessons more efficient. This article describes and justifies the advantages of using of the didactic and technical capabilities of interactive board at the classes of higher mathematics in technical university in comparison with traditional academic discipline teaching.